Editorial - Engelbrecht, Lambert K (Social Work/Maatskaplike Werk, 2023)
The third edition of 2023 presents a collection of eight articles that delve into four central themes: role players in social work, the interface of Covid-19, gender-based violence, and child rights. The articles engage with diverse challenges and dynamics within the social work landscape, contributing to the advancement of theory and practice in both local and global contexts. In this editorial, we provide an overview of the themes and the contributions each article makes to the broader discourse.